Reform of Industry Education Integration Teaching in Equipment Manufacturing Majors from the Perspective of Promoting Education through Competition - Liao, Yunfei (Transactions on Social Science, Education and Humanities Research, 2023)
At present, with the changes in teaching indicators in vocational colleges, various skills and subject competitions have become important ways to evaluate school teaching and student quality. Reconstruct teaching quality evaluation standards by combining competition evaluation standards with teaching practice; Revise daily teaching quality supervision and assessment standards based on core observation elements such as teaching design, teaching implementation, and evaluation in competitions; The construction of a teaching quality standard system that inherits concepts and policies, and connects characteristics and reality has become an important content of current vocational education. On the basis of systematically elaborating on the importance of competition course integration, this article proposes an implementation plan for competition course integration in accordance with the curriculum settings and corresponding relationships of manufacturing majors.